Quantifying environmental factors: a measure of physical, attitudinal, service, productivity, and policy barriers - Whiteneck, Gale G; Harrison-Felix, Cynthia L; Mellick, David C; Brooks, C A; Charlifue, Susan B; Gerhart, Ken A (Archives of physical medicine and rehabilitation, 2004)
To develop and test a new instrument to assess environmental barriers encountered by people with and without disabilities by using a questionnaire format. New instrument development. A rehabilitation hospital and community. Two convenience samples: (1) 97 subjects, 50 with disabilities and 47 without disability, and (2) 409 subjects with disabilities from spinal cord injury, traumatic brain injury, multiple sclerosis, amputation, or auditory or visual impairments. In addition, a population-based sample in Colorado of 2269 people (mean age, 44 y; 57% men) with and without disabilities. Not applicable. Item development; factor structure; test-retest, subject-proxy and internal consistency reliability; content, construct, and discriminant validity; and subscale and abbreviated version development. Panels of experts on disability developed items for the Craig Hospital Inventory of Environmental Factors (CHIEF). The instrument measured the frequency and magnitude of environmental barriers reported by individuals. Five subscales were derived from factor analysis measuring (1) attitudes and support, (2) services and assistance, (3) physical and structural, (4) policy, and (5) work and school environmental barriers. The CHIEF total score had high test-retest reliability (intraclass correlation coefficient [ICC]=.93) and high internal consistency (Cronbach alpha=.93), but lower participant-proxy agreement (ICC=.62). Significant differences were found in CHIEF scores among groups of people with known differences in disability levels and disability categories. The CHIEF has good test-retest and internal consistency reliability with evidence of content, construct, and discriminant validity resulting from its development strategy and psychometric assessments in samples of the general population and among people with a variety of disabilities.